Trade unions in Malta - Baldacchino, Godfrey (Brussels, 2009)
"This report on Maltese trade unions forms part of a wide-ranging ETUI project which aims to map changes in unionisation and the varying organisational structures of unions in the ‘New Member States’ (NMS). The author, Godfrey Baldacchino, indicates that Maltese trade unions still enjoy significant membership rates. More than one in two workers in Malta is a trade union member, one of the highest unionisation rates in the EU. The two main trade unions have seen the rise of different sections in their internal structures, while their dominance has been weakened."